Cultural Competence Assessment Instrument: Initial Italian validation and proposed refinement - Caricati, Luca; Dicembrino, Rita Bruna; Gionti, Luciano; Petre, Lucica; Ungurean, Liana (Acta Biomedica Atenei Parmensis, 2015)
Background and aim of the work: Italy has become a target of immigration in the last three decades. Accordingly, the Italian population is progressively changing, becoming increasingly culturally different. Cultural competences are a fundamental requirement for many industries and, especially, for healthcare organizations. The aim of this paper is to propose an initial Italian validation of the Cultural Competence Assessment Instrument (CCAI) and to propose a refinement of this scale in terms of measured constructs. Methods: The CCAI was translated into Italian through a team-based iterative approach and then administered to a sample of 289 nurses with symbolic and realistic threat scale and social dominance orientation scale. An on-line cross-sectional survey questionnaire was used. Results: Confirmatory factor analysis revealed that the original two dimensions of the CCAI can be divided into two other sub-scales, thus leaving us with the following dimensions: cultural awareness, cultural sensitivity, seeking information and active behavior. These dimensions appeared to be sufficiently reliable and independent one from another. Moreover, they showed specific and different correlations with other measured constructs. Conclusions: The Italian version of the CCAI would seem to be a useful instrument for measuring both attitudes and behavioral intention of nurses with respect to intercultural care. Using four dimensions instead of two appears to increase the understanding of professionals’ cultural competence and supply a deeper picture of dimensions which compose cultural competence in healthcare settings.